2006
DOI: 10.1128/aem.00029-06
|View full text |Cite
|
Sign up to set email alerts
|

Direct Molecular Approach to Monitoring Bacterial Colonization on Vacuum-Packaged Beef

Abstract: Denaturing gradient gel electrophoresis allowed us to monitor total bacterial communities and to establish a pattern of succession between species in vacuum-packaged beef stored at 2 and 8°C for 9 weeks and 14 days. Species-specific PCR was used to confirm the presence of Lactobacillus sakei and Lactobacillus curvatus. Multiplex PCRs using 16S rRNA-specific primers allowed differentiation between Leuconostoc species. These methods provided the desired information about microbial diversity by detecting the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…The initial numbers of LAB at 0 day were 1.768 x 10 3 , 1.831 x 10 3 , 1.818 x 10 3 , 1.845 x 10 3 , 1.836 x 10 3 for control, US-VP, US-MAP, VP and MAP treatments, respectively. The growth LAB increased with an increase in storage time, these results were in good agreement with that observed by [7]. They reported that the LAB counts increased from 10 2 to 10 6 CFU g -1 after 14 days at 8°C and 6 weeks at 2°C.…”
Section: Microbial Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…The initial numbers of LAB at 0 day were 1.768 x 10 3 , 1.831 x 10 3 , 1.818 x 10 3 , 1.845 x 10 3 , 1.836 x 10 3 for control, US-VP, US-MAP, VP and MAP treatments, respectively. The growth LAB increased with an increase in storage time, these results were in good agreement with that observed by [7]. They reported that the LAB counts increased from 10 2 to 10 6 CFU g -1 after 14 days at 8°C and 6 weeks at 2°C.…”
Section: Microbial Studiessupporting
confidence: 88%
“…They found that the pH reduced in control sample from (5.76 to 5.52). In addition, [7] also found that, the mean of the pH values in fresh beef vacuum package was decreased during storage at 2º and 8°C to final values of 5.17 ± 0.03 and 5.24 ± 0.02, respectively, the drop in pH values observed in meat samples may be attributed to the selective growth of microorganisms especially the lactic acid bacteria, which may also have contributed to the inhibition of gramnegative meat-borne organisms [7].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The rapid identification of dominant spoilage microbial which had a strong influence on the final texture and the hygienic quality of the meat products can be used to indicate which preservative methods can be applied most effectively. PCR-DGGE clearly has potential in the analysis of microbial systems from different food in which many microorganisms are difficult to cultivate or are thought to be non-culturable (Fontana et al, 2006). In this study a PCR-DGGE protocol was established for identification and characterization of the dominant spoilage bacteria of cooked meat products.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent decade, PCR-DGGE has been successfully applied to investigate the microbiology of fermented foods, such as fermented maize dough (Ampe et al, 1999), fermented sausages (Rantsiou et al, 2005), milk products (Temmerman, Masco, Vanhoutte, Huys, & Swings, 2003), etc. In recent years, monitoring the dynamics of microbial populations, and characterizing the dominant spoilage bacteria of beef or chilled pork have been studied using PCR-DGGE (Ercolini, Russo, Torrieri, Masi, & Villani, 2006;Fontana, Cocconcelli, & Vignolo, 2006;Li, Zhou, Xu, Li, & Zhu, 2006a). However, there are few data using PCR-DGGE technique to characterize the dominant spoilage bacteria in cooked meat product.…”
Section: Introductionmentioning
confidence: 99%